Isopentenyltransferase-1 (IPT1) knockout in Physcomitrella together with phylogenetic analyses of IPTs provide insights into evolution of plant cytokinin biosynthesis - Lindner, Ann-Cathrin; Lang, Daniel; Seifert, Maike; Podlešáková, Kateřina; Novák, Ondřej; Strnad, Miroslav; Reski, Ralf; von Schwartzenberg, Klaus (Journal of experimental botany, 2014)
The moss Physcomitrella patens is part of an early divergent clade of land plants utilizing the plant hormone cytokinin for growth control. The rate-limiting step of cytokinin biosynthesis is mediated by isopentenyltransferases (IPTs), found in land plants either as adenylate-IPTs or as tRNA-IPTs. Although a dominant part of cytokinins in flowering plants are synthesized by adenylate-IPTs, the Physcomitrella genome only encodes homologues of tRNA-IPTs. This study therefore looked into the question of whether cytokinins in moss derive from tRNA exclusively. Targeted gene knockout of ipt1 (d|ipt1) along with localization studies revealed that the chloroplast-bound IPT1 was almost exclusively responsible for the A37 prenylation of tRNA in Physcomitrella. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS)-based cytokinin profiling demonstrated that the total amount of all free cytokinins in tissue was almost unaffected. However, the knockout plants showed increased levels of the N (6) -isopentenyladenine (iP)- and trans-zeatin (tZ)-type cytokinins, considered to provide active forms, while cis-zeatin (cZ)-type cytokinins were reduced. The data provide evidence for an additional and unexpected tRNA-independent cytokinin biosynthetic pathway in moss. Comprehensive phylogenetic analysis indicates a diversification of tRNA-IPT-like genes in bryophytes probably related to additional functions.
Keywords: Plants; tRNA.; RNA transferová; Bryophyte; chloroplasty; fylogeneze; Phylogeny; molekulární sekvence - údaje; Chloroplasts; mechy; biologická evoluce; genový knockout; Bryopsida; Plant Proteins; moss; Cytokinins; rostliny; isopentenyltransferases; cytokininy; Gene Knockout Techniques; cytokinin; RNA, Transfer; Biological Evolution; isopentenyladenosine; Alkyl and Aryl Transferases; Molecular Sequence Data; alkyltransferasy a aryltransferasy; rostlinné proteiny